Effects of functionalized carbon nanofillers on the spectral selectivity behavior of aluminum nanocomposites for solar absorber applications - Zabri, Mohd Zakuan; Rozali, Shaifulazuar; Yahaya, Nor Afifah; Shazali, Siti Shafiah (Elsevier, 2018)
The effects of functionalized multi-walled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs) on the spectral selectivity behavior of aluminum (Al) nanocomposites were investigated in this study. The attachment of the carboxylic (COOH) functional group on the surface of the carbon nanofillers was confirmed by Fourier transform infrared spectroscopy. The pristine and functionalized MWCNTs and GNPs were introduced into pure Al powder at different concentrations (5, 10, and 15 wt%) to produce Al–MWCNT–GNP and Al–MWCNTCOOH–GNPCOOH nanocomposites. The results show that the dispersion of the carbon nanofillers is better and the spectral selectivity ratios are higher for the Al–MWCNTCOOH–GNPCOOH nanocomposites compared with those for Al–MWCNT–GNP nanocomposites. In addition, the light absorption is significantly enhanced in the ultraviolet, visible, and near-infrared regions (200–2500 nm) whereas the reflectance is significantly enhanced in the near-infrared, mid-infrared, and far-infrared regions (3000–14 000 nm) for the Al–MWCNTCOOH–GNPCOOH nanocomposites. The highest spectral selectivity ratio (27.41) is attained for the Al nanocomposite with 2.5 wt% MWCNTCOOH and 2.5 wt% of GNPCOOH.